Proceedings of IEEE International Conference on Computer Aided Design (ICCAD)
DOI: 10.1109/iccad.1995.479878
|View full text |Cite
|
Sign up to set email alerts
|

The formal verification of a pipelined double-precision IEEE floating-point multiplier

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…In [16], [17] a combination of theorem proving and symbolic trajectory evaluation [18] is used to verify multiplier designs. Both approaches decompose the general proof into several proof steps.…”
Section: Previous Workmentioning
confidence: 99%
“…In [16], [17] a combination of theorem proving and symbolic trajectory evaluation [18] is used to verify multiplier designs. Both approaches decompose the general proof into several proof steps.…”
Section: Previous Workmentioning
confidence: 99%
“…Claesen et al 98 used theorem proving to formally verify an SRT integer divider. Aagaard and Seger 99 combined model checking and theorem proving to show the correctness of an Intel multiplier. O'Leary et al 100 formally verified an SRT integer square root circuit.…”
Section: Related Workmentioning
confidence: 99%
“…Aagaard and Seger [1] combined BDD-based model-checking and theorem proving techniques in the Voss hardware verification system to verify the IEEE compliance of the gate-level implementation of a floating-point multiplier. O'Leary et al [34] reported on the specification and verification of the Intel Pentium R Pro processor's floating-point execution unit at the gate level using a combination of model-checking and theorem proving.…”
Section: Related Workmentioning
confidence: 99%
“…where v n represents the n th bit of the binary string in the fixed-point number, 1 and M and N are respectively fracbits and wordlength. In HOL, we define the valuation function value that returns the corresponding real value of a fixed-point number.…”
Section: Fixed-point Valuationmentioning
confidence: 99%